Answer:
The value of x is the given expression is
![(-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uedbvq8501byf0sj13ex7bnhla9udwbk6j.png)
Explanation:
Given equation is 28x-56=22x-65
To simplify the given equation as below:
28x-56=22x-65
Subtracting 22x on both sides we get
28x-56-22x=22x-65-22x
6x-56=-65 ( adding the like terms )
Adding 56 on both sides we have
6x-56_56=-65+56
6x=-9
Dividing by 9 on both sides
![(2x)/(3)=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8xmf08cw98cglstwrvkbq6ttcdq485abes.png)
Multiply into
on both side
![(2x)/(3)*((3)/(2))=-1*((3)/(2))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4u8749ll5pxfu8sqq4n7b01v47cxs0tzkp.png)
![x=(-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ftj77gsiioj8t3h2w63f2chcealnc6uhy7.png)
Therefore
![x=(-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ftj77gsiioj8t3h2w63f2chcealnc6uhy7.png)
The value of x is the given expression is
![(-3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/uedbvq8501byf0sj13ex7bnhla9udwbk6j.png)